Influence of friction stir processing on the microstructure and mechanical properties of a compocast AA2024-Al2O3 nanocomposite. (15th September 2016) - Hoziefa, W.; Toschi, S.; Ahmed, M.M.Z.; Morri, Al.; Mahdy, A.A.; El-Sayed Seleman, M.M.; El-Mahallawi, I.; Ceschini, L.; Atlam, A.
Abstract: The effect of friction stir processing (FSP) on the microstructure and mechanical properties of a semi-solid cast AA2024-1wt%Al2 O3 nanocomposite was investigated. For comparison, plates of unreinforced AA2024 alloy were also cast and processed at the same FSP conditions (400 rpm, 20 mm/min). The microstructure of all the produced materials was investigated using optical microscopy (OM), scanning electron microscopy (SEM) and electron backscattered diffraction (EBSD). Microhardness and tensile tests were carried out on the unreinforced AA2024 alloy and AA2024-Al2 O3 nanocomposite before and after FSP. The addition of 1 wt% of Al2 O3 nanoparticles significantly reduced the grain size of both the cast and FSPed microstructures, leading to a grain size reduction from 28 μm to 18 μm in the cast condition, and from 3.7 μm to 2.3 μm after FSP. The application of FSP to AA2024-Al2 O3 nanocomposite enhanced the tensile strength and yield strength by 71% and 30%, respectively, in comparison to the as cast matrix, as a result of the uniform distribution of Al2 O3 reinforcement and grain refinement of Al matrix. The combined application of compocasting and FSP resulted to be a promising method to treat casting defects and to produce nanocomposites characterised by good reinforcement dispersion and high strength and ductility. Graphical abstract: Highlights: Friction Stir Processing (FSP) was evaluated as means to distribute nanoparticle in a compocast AA2024-Al2 O3 nanocomposite The low wettability of nanoparticles led to porosity and particle clusters in the as cast AA2024-Al2 O3 nanocomposite The FSPed nanocomposite presented enhanced YS and UTS in comparison to the unreinforced alloy similarly processed Casting defects associated with nanoparticles addition (porosities/clusters) were eliminated by FSP The beneficial effect of FSP and Al2 O3 nanoparticles addition on AA2024 tensile strength was confirmed by this study